Pembuatan Foam Glass Menggunakan Limbah Pecahan Kaca Dan Abu Terbang (Fly Ash) Dari Pabrik Sawit - Sihombing, Ambtenarie Jessica; Fadli, Ahmad; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Foam glass can be produced using cullet and fly ash with addition of dolomite as foaming agent. The aim of this research is to study the influence of adding compositon of glass powder and dolomite on the characterize of the foam glasses and to determine the best composition of the obtained foam glass. Firstly, cullets were milled using crusher. The fly ashwere calcined at 600ºC for 4 hours. Subsequently fly ash, glass powder and dolomite were sieved using 100 mesh sieve. Furthermore, 50 %wt of fly ash, (60, 55, 50, 45, 40, 35) %wt of glass powder and 8 %wt of dolomite were mixed in 32 %wt NaOH solution until formed a slurry. The slurry was stirred for 30 minutes. Slurry was dried in oven at 105ºC for 12 hoursuntil formed the dried green bodies. Green bodies was sintered at 900ºC for 30 minutes. The results show that the glass powder addition of 35-45 %wt obtained an increase in the bulkdensity and compressive strength of the foam glass. The best microstructures of pores can be obtained by adding 45 %wt glass powder and 8 %wt dolomite with bulk density dancompressive strength values of 1.041 gr/cm3; 2.877 MPa.Keywords : compressive strength, dolomite, foam glass, glass powder, palm oil fly ash